The Semiotics of the Ekpe Masquerade: A Multimodal Analysis of Ancestral Presence and Political Authority in Cross River Cosmology - Aaron Ogbonnah Nwogu (Universitas Negeri Makassar, 2025)
The Ekpe masquerade of the Cross River basin is conventionally studied as a cultural performance, a ritual event, or a political institution. Yet it is also, and perhaps fundamentally, a semiotic event of extraordinary density, a moment when multiple sign systems, visual, auditory, kinetic, spatial, and ingestive, converge to produce the effect of ancestral presence. This article offers a multimodal semiotic analysis of the Ekpe masquerade, arguing that it constitutes a sophisticated technology for manifesting Mfam, the ancestral force that underwrites political authority and moral order in Ejagham and Efik cosmology. Drawing on Peircean semiotics, particularly the triadic division of signs into icons, indices, and symbols, and on Kress and van Leeuwen's (2001) framework for multimodal social semiotics, the study analyses the masquerade across five semiotic modes: the visual semiotics of the costume and its nsibidi embellishments, the auditory semiotics of the sacred drum and ritual silence, the kinetic semiotics of the masquerade's movement and gesture, the spatial semiotics of the lodge and the performance arena, and the ingestive semiotics of the kola nut covenant that accompanies the masquerade's appearance. Data are drawn from ethnographic fieldwork conducted in Cross River State between 2019 and 2024, including observations of twelve masquerade performances, interviews with twenty-two Ekpe initiates, and analysis of the extensive ethnographic and historical literature on Ekpe (Nair, 1972; Latham, 1973; Röschenthaler, 2011; Nwosu, 2016; Aniche, 2020). The analysis reveals that the masquerade operates through a layered semiotic strategy in which iconic resemblance (the costume as leopard), indexical pointing (the drum as ancestral voice, the kola stain as covenant seal), and symbolic convention (nsibidi signs as esoteric code) are woven together into a single, overwhelming communicative act. The article further argues that the masquerade's semiotic efficacy depends on a principle of